2003
DOI: 10.1104/pp.012732
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Autumn Leaves

Abstract: Two cDNA libraries were prepared, one from leaves of a field-grown aspen (Populus tremula) tree, harvested just before any visible sign of leaf senescence in the autumn, and one from young but fully expanded leaves of greenhouse-grown aspen (Populus tremula ϫ tremuloides). Expressed sequence tags (ESTs; 5,128 and 4,841, respectively) were obtained from the two libraries. A semiautomatic method of annotation and functional classification of the ESTs, according to a modified Munich Institute of Protein Sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
260
4
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(287 citation statements)
references
References 46 publications
16
260
4
7
Order By: Relevance
“…Similar to our ®nding in Arabidopsis, the most redundant expressed gene is the metallothionein whose transcript was 13 times more abundant in the autumn leaves as compared to young leaves (Bhalerao et al, 2003). In addition to the metallothionein, genes encoding early-light-inducible proteins (ELIP), proteases and components of the ubiquitin degradation pathway are found at the top of the list as the most abundant expressed genes in the aspen autumn leaf.…”
Section: Senescence-enhanced Gene Expression In Monocarpic Plants As supporting
confidence: 76%
See 2 more Smart Citations
“…Similar to our ®nding in Arabidopsis, the most redundant expressed gene is the metallothionein whose transcript was 13 times more abundant in the autumn leaves as compared to young leaves (Bhalerao et al, 2003). In addition to the metallothionein, genes encoding early-light-inducible proteins (ELIP), proteases and components of the ubiquitin degradation pathway are found at the top of the list as the most abundant expressed genes in the aspen autumn leaf.…”
Section: Senescence-enhanced Gene Expression In Monocarpic Plants As supporting
confidence: 76%
“…A recent genomic study aimed at understanding the molecular program of leaf senescence in autumn leaves of the aspen tree (Populus) has yielded large-scale sequencing and analysis of expressed sequence tags (ESTs) obtained by comparison of two cDNA libraries prepared from autumn and young leaves (Bhalerao et al, 2003). The information obtained from this study allows us to compare and estimate the degree of similarity between gene expressions in the two extreme variations of leaf senescence systems; monocarpic senescence as represented by Arabidopsis and autumn leaves of perennial trees.…”
Section: Senescence-enhanced Gene Expression In Monocarpic Plants As mentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have documented that plant MTs function similarly as their mammalian counterparts in metal tolerance and homeostasis and controlling ROS balance (reviewed in Cobbett et al 2002;Akashi et al 2004;Mir et al 2004;Xue et al 2009). It has also been shown that plant MTs are involved in plant stress tolerance and plant growth and development processes (Bhalerao et al 2003;Guo et 20 al. 2003;Yuan et al 2008;Xue et al 2009;Yang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, many studies have reported that plant MTs acted as protectants against oxidative stresses imposed by a dverse environmental conditions (Akashi et al 2004;Mir et al 2004;Wong et al 2004;Xue et al 2009;Samardzic et al 2010). In addition, other studies have highlighted the importance of plant MTs in plant growth and development, such as seed development 15 and germination (Brkljacic et al 2004;Yuan et al 2008), tissue senescence (Bhalerao et al 2003;Guo, Bundithya & Goldsbrough 2003), fruit ripeness (Clendennen & May 1997) and root development (Yuan et al 2008). For example, the expression of most Arabidopsis MT genes was dramatically increased in senescing siliques and leaves (Guo et al 2003).…”
Section: Introductionmentioning
confidence: 99%